CHALLENGES OF THE LIVELIHOOD EMPOWERMENT AGAINST POVERTY PROGRAMME IN THE UPPER WEST REGION OF GHANA: THE INSTITUTIONAL PERSPECTIVE - Jaha, I.R; Sika-Bright, S. (UDS International Journal of Development, 2016)
Since independence Ghana has embarked on various development strategies and programmes with the aim of reducing poverty and moving the country into a desired prosperous nation. Though initial successes were recorded making Ghana a beacon of hope in Africa these successes did not stand the test of time. Poverty reduction programmes became much popular in the 1980s with the introduction of Structural Adjustment programmes among others. However, after thirty years of implementing pro-poor programmes and policies to reduce poverty the results has been minimal with the current national poverty rate at 28.5% is an indication of a relatively high level of poverty in the country marked by widespread regional disparities. The high poverty levels also results in further social exclusion of citizens thereby widening the gap between the rich and poor. This paper focused on the specific poverty alleviation programme the livelihood empowerment against poverty implemented in the country since 2008. This paper examines the peculiar challenges that the programme faces in the Upper West region from the institutional perspective. Interviews from nine program officers from the various districts in the Upper West region provided data for this study. This was supplemented with secondary data using 2010 population and housing census, government publications on the LEAP programme, district statistics on the LEAP as well as relevant publications on LEAP in Ghana. The study revealed that some efforts have been made to hence the living conditions of the poor in the Upper West region through the programme. However the programme is challenged with administrative difficulties, irregular inflow of funds as well as perceived political interferences. Therefore, this paper recommends that poverty reduction programmes such as this should be sustained and made more efficient by improving the administrative capacity of programme officers. The study further recommends the provision of more complementary benefits to beneficiaries and also giving some non-formal education and training to beneficiaries in the best use of funds. Keywords: Poverty reduction, Livelihoods empowerment programme, Challenges, Upper West region, Institutional perspective